Genetic diversity in jamun under semi-arid ecosystem of western India (Indian Journal of Arid Horticulture, 2020)
An investigation was undertaken to evaluate the performance of 14 genotypes of jamun at Experimental Farm of Central Horticultural Experiment Station (ICAR-CIAH), Vejalpur, Panchmahals (Godhra), Gujarat under rainfed hot semi-arid ecosystem of western India during the years 2015 and 2016. These genotypes were studied to determine the variability with regards to vegetative growth, flowering and fruit quality attributes under hot semi-arid conditions. The results of study showed considerable variation with respect to vegetative, floral, yield and physico-chemical characters of fruit. The vegetative growth in terms of annual extension growth varied between 34.15 to 58.00 cm being the lowest in CHESJ-28 and the highest in CHESJ-32. The period of panicle emergence and flowering was recorded in February in almost all the genotypes. Panicle length ranged from 10.00 to 14.50 cm. The peak period of fruit set was noticed in the month of March, whereas fruit ripening started from 4" week of May and continued up to 4th week of June in different genotypes. Considerable variation in different flower organs was also observed amongst the genotypes. Flower length, breadth, calyx length, breadth ranged between 09.20-13.28 mm, 09.11-10.29 mm, 7.50-9.00 mm and 4.21-5.18 mm respectively. The maximum fruit yield (30.28 kg/ plant), fruit weight (18.00 g), pulp content (84.44%), TSS (17.42°Brix), total sugar (10.60%) was recorded in CHESJ-30. Based on the various desired traits, the genotypes, CHESJ-30 was found to be promising.
Keywords: Diversity; flower length; fruit yield; ovary; panicle length; ripening time